Religious Radicalism Prevention Model in Ma’had Al-Jami’ah at State Islamic Universities - Asa'ari Asa'ari; Rifqi Nurdiansyah; Mursal Mursal; Doli Witro; Raid Alghani (Nadwa: Jurnal Pendidikan Islam, 2022)
This article aims to formulate a strategy for preventing anti-religious radicalism at PTKIN's Ma'had al-Jami'ah in Indonesia, which is synergized with the Ma'had al-Jami'ah curriculum for the development of Ma'had al-Jami'ah. This study utilized qualitative research methods and a case study approach. This study's population was Ma'had al-Jamiah at PTKIN in Indonesia. Observation of non-participants and interviews were utilized for data collecting, with condensation, presentation, and conclusion approaches for data analysis. The findings indicated that the strategic procedures implemented by Ma'had al-Jamiah PTKIN in Indonesia involved teachers' appointments. In preventing religious extremism from Ma'had al-Jami'ah PTKIN in Indonesia, one of the most effective measures is to adjust the Ma'had management system's curriculum. In addition, the model for avoiding religious extremism in Ma'had al-Jami'ah was implemented using the teaching model based on the Islamic Yellow Book (Kitab Kuning). Furthermore, this study argued that those responsible for selecting Ma'had al-Jami'ah teachers should comprehensively understand Islam.